Secret at mystic lake - Keene, Carolyn (New York, N.Y. : Aladdin Books, an imprint of Simon & Schuster Children's Publishing Division, 2014)
To celebrate her birthday, George is taking Nancy and Bess on a bike tour around Mystic Lake, but when their tour guide disappears and unknown adversaries steal their supplies and slash their tires, Nancy begins looking for clues.
740L
Accelerated Reader AR
Keywords: Camping -- Juvenile fiction; Cycling -- Juvenile fiction; Detective and mystery stories